A Theoretical and Experimental Analysis of Rotary Compression of Hollow Forgings Formed Over a Mandrel - Tomczak, J.; Pater, Z.; Bulza, T. (Проблемы прочности, 2017)
The paper presents selected results of studies of the process of forming hollow stepped shaft forgings by rotary compression with rotary tools. The aim of the study was to determine whether rotary compression could be performed using an additional tool – a mandrel, which, when positioned in the cavity of the workpiece, could be used to shape the surface of the cavity.